Dinocyst and acritarch biostratigraphy of the Late Pliocene to Early Pleistocene at Integrated Ocean Drilling Program Site U1307 in the Labrador Sea - Aubry, Aurélie Marcelle Renée; De Schepper, Stijn; De Vernal, Anne (Journal of Micropalaeontology, 2020)
Abstract. We have analyzed marine palynomorphs (mainly dinocysts and acritarchs) from the Integrated Ocean Drilling Program Site U1307 in the Labrador Sea in order to establish a detailed biostratigraphy for the Late Pliocene to Early Pleistocene. We have defined three magnetostratigraphically calibrated dinocyst and acritarch biozones in the Late Pliocene to Early Pleistocene. Zone LS1 is defined based on the highest occurrence of Barssidinium graminosum and covers the later Pliocene from 3.21 to 2.75 Ma. Zone LS2 is marked by the acme of Pyxidinopsis braboi which occurs between 2.75 and 2.57 Ma, thus encompassing the Plio–Pleistocene transition. Finally, zone LS3 extends from 2.57 to 2.23 Ma in the Early Pleistocene. The palynostratigraphic record of IODP Site U1307 is difficult to correlate to other North Atlantic and Nordic Seas sites mainly because of a different temporal resolution and a lack of well-defined biostratigraphic marker species at the basin scale. The low abundance, discontinuous occurrence and asynchronous events of warm-water Pliocene taxa such as Invertocysta lacrymosa, Impagidinium solidum, Ataxiodinium confusum, Melitasphaeridium choanophorum and Operculodinium? eirikianum suggest cooler conditions in the Labrador Sea than elsewhere in the North Atlantic, reflecting a strong regionalism. Nevertheless, as recorded at other locations in the North Atlantic, the disappearance of many dinocyst and acritarch taxa around 2.75 Ma at Site U1307 reflects a strong ecological response accompanying the intensification of the Northern Hemisphere glaciation.

An overview and brief description of common marine organic-walled dinoflagellate cyst taxa occurring in surface sediments of the Northern Hemisphere - Van Nieuwenhove, Nicolas; Head, Martin J.; Limoges, Audrey; Pospelova, Vera; Mertens, Kenneth N.; Matthiessen, Jens; De Schepper, Stijn; De Vernal, Anne; Eynaud, Frédérique; Londeix, Laurent; Marret, Fabienne; Penaud, Aurélie; et al. (Marine Micropaleontology, 2020)

Distribution of common modern dinoflagellate cyst taxa in surface sediments of the Northern Hemisphere in relation to environmental parameters: The new n=1968 database - De Vernal, Anne; Radi, Taoufik; Zaragosi, Sebastien; Van Nieuwenhove, Nicolas; Rochon, André; Allan, Estelle; De Schepper, Stijn; Eynaud, Frédérique; Head, Martin J.; Limoges, Audrey; Londeix, Laurent; Marret, Fabienne; et al. (Marine Micropaleontology, 2020)